Markers of social difference and student permanence in the higher education: notes and tensioning - Silva, Alexandro (Revista Hipótese, 2016)
This article discusses the implementation of public policies in higher education from incidents issues in federal schools. Puts into perspective intersectional educational policies, student experiences and institutional management as a strategy to think maintenance possibilities and break the uneven condition that characterizes the Brazilian society. Through an ethnography on a campus of a federal university, gathers observations, reports and summaries of reasons and motives of seeking psychological care to present indicator notes the approach of some university context of the phenomena that keeps the tension between students, university and society.
Keywords: Student Permanence; Social markers of difference; Gender; Gender identity